Mempertahankan Kepercayaan Publik: Peran Utama Majelis Pengawas Notaris dalam Penanganan Laporan Masyarakat - Tsaniya Hafizha (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
As a professional body that manages notary services, the Notary Supervisory Board is responsible for maintaining the integrity and quality of notary services in handling public reports. This is done in order to maintain public trust. This research will be carried out with the aim of being able to see about the role of the Notary Supervisory Board in handling reports originating from the public so as to be able to maintain public trust. This research will be carried out using a descriptive qualitative approach. The results of this study found that the Notary Supervisory Board has the function and responsibility to be able to handle public reports effectively. This is done to maintain public trust in the notary profession. However, in its implementation the Notary Supervisory Board has several problems, both internal and external problems. Therefore, there is a need for a specific strategy that can be implemented to increase transparency and accountability in the handling process, improve communication and collaboration with the community.